Peluang Transfer Antar Generasi pada Usaha Perkebunan di Sumatera Selatan, Indonesia - Adriani, Dessy; Maryadi, Maryadi; Purbiyanti, E.; Huanza, M.; Damayanthy, D.; Sulastri, Merna A.; Wahyuni, R.; Novitasari, S.; Septiani, D.; Setiabudi, A. (Seminar Nasional Lahan Suboptimal, 2023)
Adriani, D., Maryadi, M., Purbiyanti, E., Huanza, M., Damayanthy, D., Sulastri, M. A., Wahyuni, R., Novitasari, S., Septiani, D., Setiabudi, A. (2023). Probability of intergenerational transfer in plantation business, South Sumatera Indonesia. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 673-682).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Rubber and palm oil plantations in Indonesia are the main plantation commodities that have an important role in terms of both social and economic terms. Rubber and palm oil is an export comoditiy that is able to contribute to efforts to increase the country‟s foreign exchange. The purpose of this research were: (1) to analyze the characteristics of children of plantation farmers, and (2) to analyze the perception of farmers' children in continuing plantation farming.  The research was carried out at the end of December 2021 in Banyuasin III District, Banyuasin and Tanjung Lubuk District, Ogan Komering Ilir Regency. The research method used was a survey method by interviewing children in productive age child in 2 village. The sampling method used was a proposionate stratified random sampling method. The samples taken in this study were 67 samples. The results showed that  Characteristics of children of plantation farmers in the dominant age are 15-17 years, education are junior high school graduates, dominated by women with a percentage, the length of time farmer children participate in family farming on average is about 3 years. The perception of children of rubber farmers in continuing rubber farming is in the criteria of being less interested with a total average score of 53.25. It means that in, there is an intergenerational transfer of agricultural business. However, it still requires guidance from both the family and counseling to reassure the perception of the farmer's children. The interest of children in continuing oil palm farming is in the criteria of being less interested with an average total score of 53.61, meaning that in farmer regeneration activities also took place in palm oil plantation. However, they still need guidance from both the parents' families and through agricultural counseling to reassure the interest of farmer children.